The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1080/15476286.2017.1397870
|View full text |Cite
|
Sign up to set email alerts
|

Highly motif- and organism-dependent effects of naturally occurring hammerhead ribozyme sequences on gene expression

Abstract: Recent bioinformatics studies have demonstrated a wide-spread occurrence of the hammerhead ribozyme (HHR) and similar small endonucleolytic RNA motifs in all domains of life. It is becoming increasingly evident that such ribozyme motifs participate in important genetic processes in diverse organisms. Although the HHR motif has been studied for more than three decades, only little is known about the consequences of ribozyme activity on gene expression. In the present study we analysed eight different naturally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 61 publications
2
19
0
Order By: Relevance
“…After normalizing the fold-reduction levels by accounting for the loss of gene expression, we observed that some ribozyme constructs (most notably the 5’UTR constructs) reduced gene expression more weakly compared to that data prior to normalization (Figures 2A/C). In general, the ribozymes/upstream competing sequences were observed to reduce gene expression more strongly in HEK293T cells compared to Drosophila embryos (Figures 2 and 3), which has also been observed in recent work (41). This difference could be due to different biological machinery between mammalian and insect models, different experimental assays, or the constructs themselves, as they contain different promoters and reporter genes.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…After normalizing the fold-reduction levels by accounting for the loss of gene expression, we observed that some ribozyme constructs (most notably the 5’UTR constructs) reduced gene expression more weakly compared to that data prior to normalization (Figures 2A/C). In general, the ribozymes/upstream competing sequences were observed to reduce gene expression more strongly in HEK293T cells compared to Drosophila embryos (Figures 2 and 3), which has also been observed in recent work (41). This difference could be due to different biological machinery between mammalian and insect models, different experimental assays, or the constructs themselves, as they contain different promoters and reporter genes.…”
Section: Discussionsupporting
confidence: 85%
“…mammalian vs. yeast) and experimental setups (e.g. in vitro vs. in vivo ) (41), which show that cellular context is likely important for the observed activity. Another possibility is that Mfold and Sfold are not accurately capturing RNA folding.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the resulting signal is independent of the fate of the mRNA after gRNA release. Given the hammerhead ribozyme has a rate constant for self-cleavage of 1.5 per minute (Wurmthaler et al, 2018), gRNA abundance is not expected to reflect the half-life and stability of most yeast mRNAs, which have a median half-life of 3.6 minutes (Chan et al, 2018). By contrast, standard methods usually used in eQTL mapping quantify mRNA at steady state, which may explain some of the differences we observed between our mRNA-QTLs and known eQTLs identified by RNA sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been reported that ribozyme activity in living cells are not highly correlated among different cell types (bacteria, yeast, or mammalian cells) which is understandable considering the differences in translational mechanism, intracellular environment (RNA binding proteins, ribonucleases, etc. ), and mode of gene regulation by ribozymes in different cell types [17 ]. Because high-throughput screening of riboswitches directly in mammalian cells is technically challenging, alternative design strategies focusing on aptazymes that function in mammalian cells are desirable.…”
Section: Controlling Mrna Cleavage By Aptazymesmentioning
confidence: 99%